2021
DOI: 10.3390/v13071226
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses in Bats: A Review for the Americas

Abstract: The SARS-CoV-2 coronavirus is the focus of attention as it has caused more than three million human deaths globally. This and other coronaviruses, such as MERS-CoV, have been suggested to be related to coronaviruses that are hosted in bats. This work shows, through a bibliographic review, the frequency of detection of coronavirus in bats species of the Americas. The presence of coronavirus in bats has been examined in 25 investigations in 11 countries of the Americas between 2007 and 2020. Coronaviruses have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…High levels of CoV diversity were found, which is expected, given that 75% of bat living genera are found in this region ( 1 ) and that bat-CoV diversity correlates with host taxonomic diversity. This is further supported by the fact that Brazil harbors the richest diversity of bat-CoVs found to date in the region ( 14 ; this study) as well as the highest levels of bat species richness at a global scale ( 21 ) ( Fig. 7 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…High levels of CoV diversity were found, which is expected, given that 75% of bat living genera are found in this region ( 1 ) and that bat-CoV diversity correlates with host taxonomic diversity. This is further supported by the fact that Brazil harbors the richest diversity of bat-CoVs found to date in the region ( 14 ; this study) as well as the highest levels of bat species richness at a global scale ( 21 ) ( Fig. 7 ).…”
Section: Discussionsupporting
confidence: 70%
“…The emergence of SARS-CoV-2 highlights the relevance of bat-CoVs to global health and why understanding their origin and patterns of CST is crucial for pandemic preparedness ( 13 ). In the Americas, bat-CoVs have been detected in 11 countries as of 2021 ( 14 ). Both alpha and betaCoVs have been reported, with a predominance of the former ( 15 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of our study is the discovery of Bat‐CoV in three new Neotropical bat species ( D. ecaudata , P. hastatus , and A. cinereus ) (Hernández‐Aguilar et al., 2021). Additionally, we identified the co‐circulation of four Alphacoronavirus subgenera in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to elsewhere in the world, comparably little surveillance for bat CoVs have been performed in the Americas. The vast majority, 89%, of New World CoVs are alpha-CoVs, which includes all CoVs identified in Eptesicus [17]. Here we identified 12 CoV-positive E. fuscus using pan-CoV primers, all of which were EbCoV, suggesting little CoV diversity in E.fuscus in the upper Midwest.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, metagenomic analysis of E. fuscus, M. lucifugus, and Perimyotis subflavus bats from the Eastern U.S. identified alphaCoV sequences originating from at least three viruses [16]. More broadly, a review of bat CoVs detected in the Americas found that 89.4% of the 151 CoVs described belonging to Alphacoronavirus, with the remainder in Betacoronavirus [17].…”
Section: Introductionmentioning
confidence: 98%